The Effect of Publication Media and Negative E-Wom On Employees Work Motivation UD. Sumber Indah Livestock Company in Pandemic Covid-19 - Nasir, Naufal Firhan (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study attempts to analyze the effect of publication media and negative e-wom on employeeswork motivation UD. Sumber Indah livestock company in the covid-19 pandemic. The study is publicationmedia (X1), negative e-wom (X2), and motivation (Y). Publication media has six basic principles based oncontent of the news in the publicity. Hence, these sixth principle can be measuring instrument or thesuccessful publication by the media, consisting, creativity, quantity, visibility, understandable legality. Inthat second independent variable is a negative e-wom, which has 3 indicators including intensity, a valenceof opinions, and content. While in the dependent variable (Y) Work motivation, which has 3 indicatorsincluding the direction to behavior, persistence, and level of effort. The analytical tool used multiple linearregression analysis. The population in this study were all employees of UD Sumber Indah, totaling 97respondents, so the sampling technique in this study was a saturated sampling technique. The resultsshowed that the media publication variables and negative e-WoM had a significant and partial effect onwork motivation of the employees of the UD Sumber Indah livestock company with a significance value of0.000 each.